The MSA sequence of Diepkloof and the history of southern African Late Pleistocene populations. - (:unkn) unknown (My University, 2013)
This paper presents the first multidisciplinary synthesis of the Middle Stone Age sequence of Diepkloof Rock Shelter (South Africa). We explore the main cultural changes that characterized southern African hunter-gatherer societies from OIS 5 to the beginning of OIS 3. We discuss the tempo of these changes, test the current interpretative hypotheses and explore an empirical model to explain the early appearance of symbolic marking within the Pleistocene hunter-gather societies of southern Africa. Major technological and cultural innovations appear in one form or another during OIS 5 in southern Africa, a period characterized by the coexistence of multiple, distinct technological traditions. We argue that the formation of regional identities in southern Africa would have favoured and increased cultural interactions between groups at a local scale, providing a favourable context for the development and diffusion of innovations. In the West Coast of South Africa, the main cultural innovations appear within the Howiesons Poort. It is within this context that we postulate a change in regional networks and population dynamics, leading to the success of the HP technology across southern Africa. The southern African data suggest that the history of modern humans has been characterized by multiple and independent evolutionary trajectories and that different paths and scenarios existed towards the adoption of 'modern' hunter-gatherer lifestyles.
Keywords: African Research